Effects of Improving Forest Road Standards on Shortening the Arrival Time of Ground-based Firefighting Teams Accessing to the Forest Fires - Akay, Abdullah Emin; Podolskaia, Ekaterina S; Uçar, Zennure (Forest Engineering and Technologies Platform, 2021)
In fighting against forest fires, it is crucial for the ground-based firefighting team to reach a fire area in critical response time in which the chance of controlling the fires is significantly high. Road networks are the key infrastructures that provide access to the forest areas for the protection of forest resources. In order to benefit from this important function of roads, especially in forested areas with high natural forest fire risk, they should be built in with adequate technical road standards since the low standards limit the fire truck speed that increases the arrival time of the firefighting team to the fire areas. Most of the forest roads in Turkey are Type-B secondary forest roads with low technical road standards (road width, curve radius, surface materials) that limit the speed of fire trucks. This paper aimed to evaluate the potential contribution of improving the standards of Type-B secondary forest roads in terms of increasing accessible forested areas in critical response time in the case of forest fire occurrence. The study area was Kahramanmaraş Forestry Enterprise Directorate (FED), where forests are sensitive to forest fires at the first degree. In the solution process, firstly, accessible forest areas by the firefighting teams located in the study area (six teams) according to the critical response time were determined by considering the existing road network in the study area. In the second scenario, the possible increase in the accessible forest areas with improved forest road standards and increased travel speed in forest roads was investigated. The results indicated that the areas that can be reached promptly by the firefighting teams in critical response time were 21% and 44% for considering existing roads and improved roads in the whole study area. On the other hand, the accessible forested areas in critical response time increased from 17% to 36% when standards of the forest roads were improved. It is indicated that improving road standards has a significant value to contribute the efficiency of firefighting activities if the practitioners implemented presented methodology.
Keywords: critical response time; firefighting; forest fires; Forest roads; road standards